Factors associated with high burden in caregivers of older adults with cancer. Issue 18 (4th June 2014) - Hsu, Tina; Loscalzo, Matthew; Ramani, Rupal; Forman, Stephen; Popplewell, Leslie; Clark, Karen; Katheria, Vani; Feng, Tao; Strowbridge, Rex; Rinehart, Redmond; Smith, Dan; Matthews, Keith; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Older adults with cancer are vulnerable to functional decline, which places greater onus on caregivers. Few studies have prospectively examined burden in caregivers of older cancer patients. The objective of this study was to determine the factors associated with high caregiver burden. METHODS In total, 100 caregivers of patients aged ≥65 years with cancer, who were recruited at a single institution, completed questionnaires gauging their perception of the patient's physical, emotional, and social health. The association between these items, cancer‐related factors, sociodemographic factors, and caregiver burden (measured using the Caregiver Strain Index [CSI]) was determined through multivariate analysis. RESULTS The median patient age was 70 years (range, 65‐91 years), 70% of patients had advanced disease, and 98% were receiving treatment. Caregivers were mostly women (73%), spouses (68%), and lived with the patient (79%). The median amount of care provided was 10 hours per week. The mean CSI score (± standard deviation) was 3.1 ± 3.2. Most caregivers (75%) reported some burden, with 15% reporting high caregiver burden (CSI score, ≥7). In multivariate analysis, employed caregivers (odds ratio, 4.5; 95% confidence interval, 1.1‐18.4; P = .04) and those caring for patients who required more help with instrumental activities of daily living (Older Americans Resources and Services‐Instrumental Activities of Daily Living score, <12 of a possible 14; odds ratio, 12.4; 95% confidence interval, 2.4‐62.5; P < .001) were more likely to experience high caregiver burden (CSI score, ≥7). CONCLUSIONS Caregiver burden is common in those who care for older cancer patients. High burden is more likely in employed caregivers and in those who care for patients who require increased functional assistance. Further studies are needed to determine the unique challenges experienced by caregivers of older adults with cancer and potential interventions to alleviate burden in these caregivers. Cancer 2014;120:2927–2935. © 2014 American Cancer Society.